ELEMEN-ELEMEN ARSITEKTUR NEO-GOTIK PADA GEREJA POUK LAHAI ROI JAKARTA - Milleni, Sylvia; Sudianto Aly, C (Jurnal Riset Arsitektur, 2023)
Abstract - POUK Lahai Roi Church is an Ecumenical Church located in Jakarta. At a glance, you can see elements of neo-Gothic architecture in this church, such as the tower, pointed arch, rose window, and other elements. The church, which was completed in 2007, is included in a new building that is interesting to study further because of the discovery of elements of neo-Gothic architecture which is an architectural style that developed in its final era. This study was made to identify the elements of neo-Gothic architecture found in the POUK Lahai Roi Church based on theories regarding neo-Gothic architecture. The elements of neo-Gothic architecture studied in this study based on literary sources are the roof, the ribbed vault, tower, infill wall, molding, stained glass, tracery, sculpture, door, window, rose window, column, porch, spatial arrangement, arches, materials, and colors. The analysis in this research was conducted by studying the elements of neo-Gothic architecture and then comparing them with the elements in the POUK Lahai Roi Church. Based on the analysis, found 13 elements of the 17 elements of neo-Gothic architecture in POUK Lahai Roi Church. The thirteen elements consist of the roof, the ribbed vault, tower, infill wall, stained glass, tracery, sculpture, rose window, porch, spatial arrangement, arches, material, and color, while the four elements that are not in accordance with neo-Gothic architecture are moldings, doors, windows, and columns. Thus, it can be said that the POUK Lahai Roi Church has a neo-Gothic architectural style. Keywords: element, architecture, neo-Gothic, Cijantung Jakarta